2022
DOI: 10.3389/fncel.2022.823320
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Mononuclear Cell Treatment for Neonatal Rats With Hypoxic Ischemia

Abstract: BackgroundHypoxic-ischemic encephalopathy (HIE) occurs when an infant’s brain has not received adequate oxygen and blood supply, resulting in ischemic and hypoxic damage. Currently, supportive care and hypothermia therapy have been the standard treatment for HIE. However, there are still over 20% of treated infants died and 19–30% survived with significant disability. HIE animal model was first established by Rice et al., involving the ligation of one common carotid artery followed by hypoxia. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Although some studies reported extreme effect sizes, a leave-one-outanalyses did not indicate that the overall clear efficacy of MNC treatments in HIE animal models may be caused by single studies reporting particularly good therapeutic outcomes. Thus, there is no strong Pimentel-Coelho et al 29 de Paula et al 30 Rosenkranz et al 19 Wasielewski et al 31 Rosenkranz et al 32 Wang et al 26 Greggio et al 33 Wang et al 34 Hattori et al 35 Grandvuillemin et al 18 Nakanishi et al 36 Sato et al 37 Penny et al 38 Cho et al 39 Penny et al 40 Lyu et al 41 Note: Analysis was conducted in a total of five risks of bias domains, including selection bias (D1), performance bias (D2), detection bias (D3), reporting bias (D4), attrition bias (D5), and overall bias. Low (green circles), some (yellow circles), and high (red circles) concerns for bias, as well as no information (blue circles) are indicated.…”
Section: There Is No Indication Of a General Lack Of Mnc Efficacy Fro...mentioning
confidence: 99%
“…Although some studies reported extreme effect sizes, a leave-one-outanalyses did not indicate that the overall clear efficacy of MNC treatments in HIE animal models may be caused by single studies reporting particularly good therapeutic outcomes. Thus, there is no strong Pimentel-Coelho et al 29 de Paula et al 30 Rosenkranz et al 19 Wasielewski et al 31 Rosenkranz et al 32 Wang et al 26 Greggio et al 33 Wang et al 34 Hattori et al 35 Grandvuillemin et al 18 Nakanishi et al 36 Sato et al 37 Penny et al 38 Cho et al 39 Penny et al 40 Lyu et al 41 Note: Analysis was conducted in a total of five risks of bias domains, including selection bias (D1), performance bias (D2), detection bias (D3), reporting bias (D4), attrition bias (D5), and overall bias. Low (green circles), some (yellow circles), and high (red circles) concerns for bias, as well as no information (blue circles) are indicated.…”
Section: There Is No Indication Of a General Lack Of Mnc Efficacy Fro...mentioning
confidence: 99%